Drug exporter expression correlates with group 3 innate lymphoid cell resistance to immunosuppressive agents - Omar, Said Z.; Haverkate, Nienke J. E.; van Hoeven, Vera; Blom, Bianca; Hazenberg, Mette D. (Frontiers in Hematology, 2023)
Allogeneic hematopoietic cell transplantation (HCT) is often complicated by graft versus host disease (GvHD), an alloreactive immune response triggered by tissue damage. Interleukin (IL)-22 producing type 3 innate lymphoid cells (ILC3) protect epithelial tissues against chemo(radio)therapy-induced damage, suppress alloreactive T cells and mitigate acute GvHD symptoms after allogeneic HCT.Relatively high numbers of ILC before and after allogeneic HCT has been associated with significantly reduced tissue damage and less acute GvHD. While most transplantation conditioning and GvHD prophylaxis regimens are aimed at eliminating host and alloreactive donor lymphocytes, the effect of these regimens on ILC remain elusive. Here, we studied the effect of conditioning chemotherapy and immunosuppressive agents on the survival, proliferation, activation and function of human ILC3 in vitro. Tonsil-derived ILC3 were activated and incubated with agents commonly used to prevent and treat GvHD. While fludarabine, rapamycin, mycophenolic acid and prednisolone suppressed ILC3 to a similar degree as T cells, the effect of other agents, including cyclosporine A, methotrexate, imatinib, ibrutinib and ruxolitinib, was milder on ILC3 than on T cells. ILC3 are less sensitive to immunosuppressants potentially because of their expression of functionally active ATP Binding Cassette Subfamily B Member 1 (ABCB1) drug exporter proteins. This suggests less intracellular accumulation of immunosuppressive agents, which renders ILC3 resistant to these compounds. The present findings may help to develop strategies to simultaneously maintain the tissue protective properties of ILC3 and at the same time suppress alloreactive lymphocytes, which is important in the prevention and treatment of acute GvHD.